Religious Values and Dhikr Practice as a Framework for Moral Character Building in Islamic Elementary Schools - Wildan Alan Nuril Huda; Ubaidillah; Subakri (ATTA`DIB, 2025)
Abstract This study aims to analyze the formation of students’ moral character through dzikir practices and the internalization of religious values at MI Al-Khairiyah Dusun Melik, Parijatah Kulon Village, Srono District, Banyuwangi Regency. The research is motivated by behavioral issues among students, particularly declining discipline, politeness, and self-control, highlighting the need for spiritually grounded pedagogical approaches. Using a descriptive qualitative method with data collected through in-depth interviews, participant observations, and document analysis, the study investigates the roles of teachers, school culture, and religious activities in shaping students’ character. The findings reveal that daily dzikir enhances emotional calmness, spiritual awareness, and adherence to school norms. Additionally, the internalization of religious values—instilled through habituation, modeling, and integration in Islamic education lessons—effectively fosters responsibility, empathy, and respectful attitudes among students. These results indicate that character formation becomes more effective when spiritual practices and value-based instruction are consistently embedded in school routines. The study also fills a gap in the literature regarding the use of dzikir as a pedagogical strategy in Islamic elementary education and proposes a viable model of religious-based character development for primary schools in Indonesia. Keywords: moral character, dzikir, religious values, habituation, character education. Abstrak Penelitian ini bertujuan menganalisis proses pembentukan akhlak siswa melalui praktik dzikir dan internalisasi nilai religius di MI Al-Khairiyah Dusun Melik, Desa Parijatah Kulon, Kecamatan Srono, Kabupaten Banyuwangi. Latar belakang penelitian berangkat dari fenomena degradasi perilaku siswa, terutama terkait kedisiplinan, kesantunan, dan kontrol diri, sehingga diperlukan pendekatan pedagogis berbasis spiritual untuk memperkuat karakter. Dengan menggunakan metode kualitatif deskriptif melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen, penelitian ini menelaah peran guru, budaya sekolah, serta aktivitas keagamaan dalam membentuk perilaku siswa. Hasil penelitian menunjukkan bahwa dzikir harian berkontribusi pada peningkatan ketenangan emosional, kesadaran spiritual, dan kepatuhan terhadap norma sekolah. Selain itu, pemahaman nilai religius yang diintegrasikan melalui pembiasaan, keteladanan, dan penguatan materi PAI terbukti efektif menumbuhkan tanggung jawab, empati, dan sikap hormat siswa. Temuan ini menegaskan bahwa pembentukan akhlak berjalan optimal ketika praktik spiritual dan nilai religius diterapkan secara konsisten dalam rutinitas pendidikan. Penelitian ini juga mengisi kekosongan kajian terkait implementasi dzikir sebagai strategi pedagogis pada jenjang sekolah dasar Islam dan menawarkan model pembinaan karakter berbasis religius yang relevan untuk pendidikan dasar. Kata Kunci: akhlak siswa, dzikir, nilai religius, pembiasaan, pendidikan karakter.